Buckling Performances of Spherical Caps Under Uniform External Pressure - Wang, Yueyang; Zhang, Jian; Tang, Wenxian (Journal of marine science and application, 2020)
This study aims to experimentally and numerically examine the buckling performances of stainless steel spherical caps under uniform external pressure. Three laboratory-scale caps were fabricated, measured, and tested. The buckling behaviors of these caps were investigated through experiments and three numerical methods, namely, nonlinear Riks algorithm, nonlinear bifurcation, and linear elastic analysis. The buckling of equal-radius caps was numerically analyzed with different methods to identify their applicability under different wall thicknesses. The results obtained from the nonlinear Riks algorithm are in good agreement with the experimental results, which means the nonlinear Riks algorithm can accurately predict the buckling performances of spherical caps, including the magnitude of critical buckling loads and the deformation of post-buckling modes. The nonlinear bifurcation algorithm is only suitable for predicting the buckling loads of ultra-thin or large-span caps, and the linear buckling method is inappropriate for predicting the buckling of metal spherical caps.